Receptor for advanced glycation endproducts (RAGE) is a key regulator of oval cell activation and inflammation-associated liver carcinogenesis in mice - Pusterla, Tobias; Nèmeth, Julia; Stein, Ilan; Wiechert, Lars; Knigin, David; Marhenke, Silke; Longerich, Thomas; Kumar, Varun; Arnold, Bernd; Vogel, Arndt; Bierhaus, Angelika; Pikarsky, Eli; et al. (Hepatology, 2013)
The receptor for advanced glycation endproducts (RAGE) is a multiligand receptor and member of the immunoglobulin superfamily. RAGE is mainly involved in tissue damage and chronic inflammatory disorders, sustaining the inflammatory response upon engagement with damage-associated molecular pattern molecules (DAMPs) such as S100 proteins and high-mobility group box 1 (HMGB1). Enhanced expression of RAGE and its ligands has been demonstrated in distinct tumors and several studies support its crucial role in tumor progression and metastasis by still unknown mechanisms. Here we show that RAGE supports hepatocellular carcinoma (HCC) formation in the Mdr2−/− mouse model, a prototype model of inflammation-driven HCC formation, which mimics the human pathology. Mdr2−/− Rage−/− (dKO) mice developed smaller and fewer HCCs than Mdr2−/− mice. Interestingly, although in preneoplastic Mdr2−/− livers RAGE ablation did not affect the onset of inflammation, premalignant dKO livers showed reduced liver damage and fibrosis, in association with decreased oval cell activation. Oval cells expressed high RAGE levels and displayed reduced proliferation upon RAGE silencing. Moreover, stimulation of oval cells with HMGB1 promoted an ERK1/2-Cyclin D1-dependent oval cell proliferation in vitro. Finally, genetic and pharmacologic blockade of RAGE signaling impaired oval cell activation in an independent mouse model of oval cell activation, the choline deficient ethionine-supplemented dietary regime. Conclusion: Our data identified a novel function of RAGE in regulating oval cell activation and tumor development in inflammation-associated liver carcinogenesis. (Hepatology 2013)